농업기술발전의 장기전망 - 박정근 (한국농촌경제연구원, 2007)
The purpose of this research is to find 30 years prospect of development in agricultural technology and to find the countermove corresponding to the technological change in agriculture by analyzing the related industries and their technologies which are potentially influential. The analysis is based on the future agricultural technology categorized by field, technological character, consumer propensity, and by main interest to examine the core technologies that have impact on agricultural and food industry. Increase in agricultural productivity depends more on mass production method propelled by frontier technology instead of traditional one. The traditional way focused on crop cultivating technology or livestock raising technology in order to increase the productivity. However, the future agricultural technology is lead by bioengineering technology which can improve breed to adapt the new environment or to strengthen functions in breeding field in order to increase the productivity. In input reduction sector, labor saving technology will be developed by promoting robot or harvest system. In horticulture sector, agricultural goods will be produced by the new system derived from plant factories or strengthening functions. For the input reduction technologies, it will be focused on maneuvering environment to construct the optimum yield environment instead of being adapted to the environment by change in resource endowment such as labor reduction or precision soil management. The most active sector in future agricultural technology is the one that is environment friendly to reduce pollution and develop the technology that dissolves contaminated substances. However, the future environment friendly agri-technology will not be limited to prevent the damage but be expanded to restore damaged environment. The future prospect of agri-technology is environment friendly and high quality functional agricultural product rather than traditional agricultural structural change to contrive simplicity in agricultural production. Consumption driven future agri-technology moves toward satisfying consumers need in health issues. To list a few examples, livestock breeding technology for special function, anti aging food, improvement of crops for better immune system, and blocking electromagnetic waves are expected to be developed for high end quality and functionality as medical treatment. Therefore, the agri-technology will be developed in close relation with medical knowledge in order to serve the preventive or medical function instead of consumption driven technology satisfying consumer preference on food. In the future of agriculture industry, the integrated information technology detecting hazardous substance, storage and preservation technology to keep the stability will be developed corresponding to the increase in demand of safe agricultural products. Especially, simple food products will be developed to accommodate personal taste and nutrition status and to adopt to change in life style. Therefore according to consumption driven future agri-technology, agricultural product is not just demanded in market but the food demand is designed in close relation with consumer's daily life. The future agri-technology is dominated by the technology that combines traditional agricultural method and frontier technology to consider health and environment. The main focus in future of agriculture is on how to incorporate scientific technology to agricultural technology. Researchers: Park, Jung-Keun Research period: 2007. 8. - 2007. 11. E-mail address: jkpark@chonbuk.ac.kr